Socio-economic Consequences of Canal Irrigation in an Arid District of Rajasthan - Bharara, L P (Annals of Arid Zone, 2016)
The study reveals changes in various socio-economic parameters as an ipact of canal irrigation in Ganganagar district of arid zone of Rajasthan. Based on socio-economic and historical evidences the findings prior to (1910-11 to 1920-21) and after irrigation (1927-28 to 1974-75) supported hypothesis set up on population changes, land use attributes and agriculture development, irrigation drought immigration resulting in tremendous increase of population (18.74%) and density (17.20%) persons/sq km) in the Gang Canal area during the period of 1921-71. Human settlements increases from 231 in 1921 to 1533 in 1975. Land use changes brought a decrease in degenerated lands (24.72%) and increase (192.30%) in irrigated area and net area sown (57.75%) bringing transformation of waste lands to productive lands during 1927-28 to 1974-75. Irrigated forestry, afforestation and controlled grazing took place. Changes in land ownership pattern from absolute rights of the ruler on land to absolute rights of the occupiers viz; Khatedars; cropping pattern-subsistence to commercialization; adoption of agricultural innovations and increase in ground water level (annual average 39 cm) and tube wells (44 in 1967-68 to 832 in 1972-73) encouraged agriculture development. Increase in crop productivity and reduction (mean annual 36.57%) of risk in crop failure increased the value to land from Rs. 320./- per ha in 1928-29 to Rs. 25,000/- per ha in 1974-75. Introduction irrigated fodder and availability of stall feeding the ked livestock migration, decreased mortality and increased livestock population (mean annual 0.21 million before irrigation to 0.46 million after irrigation ) sustaining higher pressure (from 44 livestock heads/ 100 ha degenerated land to 134) during the period. Reduction in degenerated lands decreased sheep population (25%) in the canal area. Rural credit system institutionalised changing attitude of the people towards use to loans fro non-productive to productive purposes.